Do Saving Rules Influence Self‐Employed Households' Participation in Tax‐Deferred Retirement Plans?. (September 2014) - Smith, Hyrum L.; Griesdorn, Tim
<x xml:space="preserve">Abstract</x> Tax‐deferred retirement (TDR) plans, including Simplified Employee Pensions, Savings Incentive Match Plan for Employees (SIMPLEs), and solo 401(k) plans, are examples of the tax advantaged plans the federal government has developed to encourage retirement savings among the self‐employed. The Survey of Consumer Finances was used to determine if families with a self‐employed worker who uses savings rules are more likely to contribute to TDR saving accounts. The analysis reveals savings rules have a positive effect on the likelihood of making retirement contributions, even after controlling for other known associated factors. Use of a financial planner, higher marginal tax rates, retirement savings motives, financial assets, and age until retirement are positively related to tax‐deferred contributions. Greater liquidity constraints and future income uncertainty are negatively related to tax‐deferred contributions. Establishing specific savings rules could help families of self‐employed workers have the tools needed for retirement preparation.